Review of Theories of Learning for Adopting - Elisabeth Sadoulet (Fondation pour les études et recherches sur le développement international (FERDI), 2016)
The diffusion of a new agricultural technology requires farmers to learn about the existence and the benefits of the technology. What do they have to learn, how do they learn it, and from whom, is the subject of a large literature, both theoretical and empirical. The purpose of this brief is to review the most prominent learning models, briefly assess recent empirical results derived from these theories, and raise a few important remaining issues not explicitly addressed by the theories.We will focus on the literature that refers to learning from experience, either own or that of others, giving prominence to the network of connections that farmers have. This review is purposefully very selective, with the objective of illustrating concepts and categories of models, rather than providing a genuine literature review. Document de travail préparé pour l'atelier Ferdi - SPIA Innovations agricoles : apprendre pour adopter, organisé à Clermont-Ferrand (France), les 1er et 2 juin 2016.
Keywords: 330